Man, gods, and nature - Dudley, Michael Kioni (Honolulu, Hawaii : Na Kane O Ka Malo Press, 1990)
"In the tropical paradise of ancient Hawaii, man, gods, and nature formed a consciously interacting and interrelating cosmic community. All of the species of nature were thought to be sentient--capable of knowing, choosing and acting. Through evolution, all were related as kin. Hawaiian lives in a community in which man, gods, and nature cared for each other and watched over and protected each other as family: they felt a sense of belonging and "at homeness" in the world which is unknown to Westerners. Book I of 'A Hawaiian Nation' discusses this fascinating view of reality."
A fish story-- Passing on knowledge in ancient Hawai'i-- The Hawaiian view of the universe-- Spirit and matter in Hawaiian thought-- Evolutionary theory in Polynesia-- Modern corroboration of sentience in nature-- Akua, mana and divinity-- Kino Lau: assuming multiple forms-- Pairing in the universe-- Environmental ethics in Hawai'i-- The special place of the chief-- The true meaning of the state motto of Hawai'i
Includes bibliographical references
Keywords: Hawaii -- Civilization; Hawaiian philosophy; Civilization